(3TQM bUjOI ddQGaYis - (3CMeO Hf eMeO Hf YLjHI GdTQja GdMSfjs
(3ChdgG (B:s
(3fMeOc jG ef JYGXeJ CfhGQ LeGdg hHgGFg hHYO abO SCdfi HYV Cgd GdeMHI Cf CVY JbjjOkG Ydi bUjOI JfJSH ddEeGe GdQGaYi s
(3BNQgG (B:s
(3hCeG GdeYQaI adG JMUd EfeG HYO GdJQHjI hGdJCPjH hGdJgPjH efMfG Gddg ef eYQaJg GdcGedI Ch ai fUjH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs